2022
DOI: 10.1177/11206721221074203
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice towards glaucoma among glaucoma patients at University of Gondar Tertiary Eye Care and Training Center

Abstract: Background For better treatment outcome, exploring the knowledge of glaucoma and practices among glaucomatous patients is much more important. Objective The aimed of this study was to determine the knowledge and self-care practice and their associated factors towards glaucoma and its medications among glaucoma patients. Methods Cross section design study was conducted between May and July, 2017. The data was collected from glaucoma patients. Descriptive statistics was done to summarize socio demography data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This was consistent with studies done in Ethiopia [13,14]. This might be because urban residents had good knowledge about glaucoma and the importance of adherence to topical anti-glaucoma medications [22]. Urban residents also have better access to eye care centers and pharmacies for replenishment when they run out of medications before their next visit.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…This was consistent with studies done in Ethiopia [13,14]. This might be because urban residents had good knowledge about glaucoma and the importance of adherence to topical anti-glaucoma medications [22]. Urban residents also have better access to eye care centers and pharmacies for replenishment when they run out of medications before their next visit.…”
Section: Plos Onesupporting
confidence: 88%
“…This result is supported by the study done in Ethiopia [15]. The reason for this may be because patients with higher educational level might easily understand the prescribed regimen [23] might have good knowledge about the importance of medication adherence [17,22,24] and may take reminder notes.…”
Section: Plos Onementioning
confidence: 56%
“… 31 The association could be explained in a way that, participants with lower educational status might not have adequate information on the nature of the disease. 32–34 Thus, they could not adopt a good practice pattern 35 (better coping mechanism) and this ultimately compromises their vision-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 86% of the participants from south India had undergone screening for glaucoma, while only 5% of the participants from Nigeria had done so (12,14). According to previous studies, some of the factors that contributed to low level of knowledge to glaucoma were living in rural areas, being single, having lower level of education, and having early stages of glaucoma (10,11). The proportion of knowledge for glaucoma varies throughout African nations, even though the World Health Organization recommends glaucoma screening examinations every 2-4 years for people under the age of 40, every 2-3 years for those between the ages of 40 and 60, and every 1-2 years for people over the age of 60 (2).…”
mentioning
confidence: 99%